Putting Elihu in his Place: A Proposal for the Relocation of Job 32–37 - Clines, David J. A. (Journal for the study of the Old Testament, 2004)
The proposal is that the Elihu speeches (Job 32–37) originally preceded Job 28. The effects of this rearrangement are (1) that Yahweh speaks directly after Job has concluded his final speech (Job 29–31), (2) that the ‘poem on wisdom' (Job 28) can be identified as the conclusion of the Elihu speeches, with which it has much in common, and (3) that four difficulties in the wording of 32.1-2 can be overcome if Elihu's intervention immediately follows the speeches of the other friends. Finally, on the basis of the arrangement of columns in the Qumran Isaiah scroll (1QIsa) an explanation is offered for how the physical displacement of these chapters in a Job scroll could have occurred in antiquity.